2009
DOI: 10.1074/mcp.m800213-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Antibody Cross-reactivity among Infectious Gram-negative Bacteria Revealed by Proteome Microarray Analysis

Abstract: Antibodies provide a sensitive indicator of proteins displayed by bacteria during sepsis. Because signals produced by infection are naturally amplified during the antibody response, host immunity can be used to identify biomarkers for proteins that are present at levels currently below detectable limits. We developed a microarray comprising ϳ70% of the 4066 proteins contained within the Yersinia pestis proteome to identify antibody biomarkers distinguishing plague from infections caused by other bacterial path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…However, previous studies demonstrated that many commercially available mAbs cross-react extensively with other cellular antigens, and some may not even recognize their purported targets. [4][5][6][7] To analyze the specificity of antibodies generated against viral, 8 microbial 9,10 and mammalian proteins, 11-14 a protein microarray-based approach has been previously reported to determine potential cross-reactivity. For example, protein microarrays, composed of protein epitope signature tags (PrESTs), have been implemented as part of the Human Protein Atlas projects, one of the several ongoing large-scale efforts to systematically identify high-grade antibodies against much of the human proteome.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies demonstrated that many commercially available mAbs cross-react extensively with other cellular antigens, and some may not even recognize their purported targets. [4][5][6][7] To analyze the specificity of antibodies generated against viral, 8 microbial 9,10 and mammalian proteins, 11-14 a protein microarray-based approach has been previously reported to determine potential cross-reactivity. For example, protein microarrays, composed of protein epitope signature tags (PrESTs), have been implemented as part of the Human Protein Atlas projects, one of the several ongoing large-scale efforts to systematically identify high-grade antibodies against much of the human proteome.…”
Section: Introductionmentioning
confidence: 99%
“…Binary Protein-Protein Interactions-We utilized a protein microarray (18) that comprised Ͼ85% of the predicted Y. pestis proteome to identify protein interaction partners (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…1A). The microarrayed proteins were expressed in vitro as recombinant GST-fusions from DNA sequence-confirmed plasmid clones and printed on glass slides that were coated with a thin layer of nitrocellulose, as previously described (18). Because the proteomes of Y. pestis and E. coli share ϳ50% of proteins with Ͼ60% amino acid identity (28, 29), we examined two reported AP-MS data sets of E. coli PPi (6, 7) to select protein probes that were common to both species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations